1998
DOI: 10.4141/p97-078
|View full text |Cite
|
Sign up to set email alerts
|

Population bulk versus F1-derived family methods of yield testing in early generations of multiple-parent interracial and inter-gene-pool crosses of common bean

Abstract: To simultaneously improve qualitative and quantitative agronomic traits, markers and gamete selection can be used. However, the effectiveness of alternative methods of yield testing in early generations must first be investigated. In this study, we therefore determined the relationships between seed yield of F1-derived families and of population bulks in F2 and F3 generations. We also compared seed yields of a high-versus low-yielding population in F2 and F3 with their advanced generation (F7) lines. First, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The common denominator in the above studies was that early generations were advanced in NS environments and seed yield and other data were collected in DS and NS environments on advanced-generation lines (genetically fixed lines), and multi-environments (years and/or locations) were used to select for drought resistance. Similarly, Singh et al (1990), Singh and Terán (1998), and Singh and Urrea (1995) were able to identify high-yielding populations and families within populations from early generation yield tests in NS environments to subsequently select high-yielding lines. Nonetheless, in each of these instances, multi-location data collected from comparatively larger plots than used in this study were used to select high-yielding lines.…”
Section: Resultsmentioning
confidence: 99%
“…The common denominator in the above studies was that early generations were advanced in NS environments and seed yield and other data were collected in DS and NS environments on advanced-generation lines (genetically fixed lines), and multi-environments (years and/or locations) were used to select for drought resistance. Similarly, Singh et al (1990), Singh and Terán (1998), and Singh and Urrea (1995) were able to identify high-yielding populations and families within populations from early generation yield tests in NS environments to subsequently select high-yielding lines. Nonetheless, in each of these instances, multi-location data collected from comparatively larger plots than used in this study were used to select high-yielding lines.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, most, if not all, commonly used crop breeding methods have been employed with common bean. However, objective data comparing the efficiency of different selection methods, with few exceptions (Beaver and Kelly, 1994; Gutiérrez and Singh, 1992; Singh and Terán, 1998; Urrea and Singh, 1994, 1995) are not available. Urrea and Singh (1994) found that the F 2 ‐derived family method of selection was superior to the SSD and bulk methods commonly used for advancing early generation of hybrid populations.…”
Section: Broadening the Genetic Base Of Common Bean Cultivarsmentioning
confidence: 99%
“…Singh and Urrea (1995) and Singh et al (1990) suggested selection for seed yield in early generation of interracial and intergene pool populations to identify promising populations with desirable recombinants. From early generation yield tests (F 2 –F 4 ), Singh and Terán (1998) identified high‐ and low‐yielding populations that eventually produced high‐ and low‐yielding advanced generation (F 7 ) lines.…”
Section: Broadening the Genetic Base Of Common Bean Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation